MOTIVASI MAHASISWA UNIVERSITAS RIAU DALAM MENGIKUTI ORGANISASI PERGERAKAN MAHASISWA ISLAM INDONESIA (PMII) - M. Ainur Rafiq; Yoskar Kadarisman (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2023)
This study discusses about the mortivation of Riau University students in joining the Indonesian Islamic Student Movement Organization (PMII). PMII is a large organization that has the largest member base in Indonesia, PMII-at the Univerrsity of Riau is not very advanced and has several times stuck in its management, so that cadre formation does not run optimally, but it was found that several Riau University students joined PMII. This study aims to find out what the motivations of Riau Universitty students are in joining the Indonesian Islamic Student Movement (PMII) organization. This study used a descriptive qualitative method, and involved 4 informants who were Riau University students who joined PMII, and 1 (one) Key Informan who was an administrator from PMII Riau University Commissariat. Determination of informants using purposive sampling technique. Data collection techniques are carried out by observation, interviews, and documentation. The results of this study indicate that there are environmental factor, ideological factors, the desire for achievement, network expansion, and power in the organization which are the driving factors for joining the PMII organization. Keywords: Motivation, Students, Joining Organizations, PMII